New comparative government: a concise study of domestic politics around the world - Johari, J.C (New Delhi, 2010)
Book Summary of New Comparative Government The study of comparative government is as old as Aristotle- the celebrated 'father of politics.' But in recent times it has assumed its own significance due to remarkable development in the spheres of national and international politics. The decline of the authoritarian systems and instead spread of democracy around the world, battle between freedom and equality importing new meaning and dimensions to the concept of 'power', transformation of the Westphalian model of the nation ? state noticeable in the emergence of 'civil society' and in the model of a trans-national state' may be referred to in particular. Global comparisons have become the fashion of the day which reveals astonishing facts about the role of political and para-political institutions. Comparing institutions as such, as done by the old writers, is not so important now. What is needed is that the scope of such a venture should be widened so as to investigate and analyse the states in the context of their actual working in the present age of liberalization and globalisation. Human action is guided fundamentally by the institutions that the people construct and change them in response to the needs of the time. A student of this subject is, therefore, expected to comprehend and analyse political reality in the light of new developments. About the Author J.C. Johari has been associated with the teaching of Political Science for more than forty years in colleges affiliated to Agra and Delhi Universities. For a year (1971-72) he worked as Deputy Director at the Institute of Constitutional and Parliamentary Studies, New Delhi. He has written a number of books on various courses of Political Science and his articles have been published in a number of research journals in India and abroad.
Keywords: Politics and government